INDIVIDUAL METHODS OF HEALTH EDUCATION IMPROVING KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN ABOUT HEPATITIS B - Sri Yanniarti; Nova Revika; Desi Widiyanti; Wewet Savitri; Else Sri Rahayu (Proceeding B-ICON, 2022)
Hepatitis B in pregnant women causes coagulation effects, organ failure, and increased maternal mortality, while in newborns, it causes asphyxia and low birth weight. Pregnant women need to know about Hepatitis B and have a positive attitude to prevent transmission to pregnant women. It can be improved through health education. This study aims to determine the effect of individual method health education with leaflet media on increasing knowledge and attitudes of pregnant women about Hepatitis B at the Sidodadi Health Center Bengkulu Tengah in 2022. The research design was quasi-experimental with a non-equivalent control group design, with a pre-test post-test control group approach. The population is all pregnant women in the area of the Sidodadi Health Center in 2022, amounting to 37 people, using the Lemeshow formula, a sample of 34 respondents (17 in intervention groups and 17 in comparison). Data were analyzed using the dependent T-test, and Wilcoxon signed rank test. There is a difference in the average knowledge score and attitudes before and after being given individual method health education with leaflet media. There is a significant difference between the two groups with ?= 0.000. It means that there is a significant effect on individual method health education with leaflet media on knowledge and attitudes of pregnant women about Hepatitis B at the Sidodadi Health Center in 2022, with a mean difference of 3.47 on the knowledge variable and 5.65 on the attitude variable. A diversity of counseling methods is needed to increase the knowledge and attitudes of pregnant women about Hepatitis B. Health workers must increase their role in improving methods and media in providing counseling to pregnant women to prevent transmission of Hepatitis B.